PERAN LINTAS BELAJAR PADA MATERI POLA BILANGAN MENGGUNAKAN KONTEKS TARIAN KHAS PALEMBANG (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
This research aims to produce a learning activity trajectory that can assist students in learning number sequences. This research is related to the 2013 curriculum and PMRI. The method used is Design Research, which consists of three stages: Preliminary Design, Design Experiment, and Retrospective Analysis. This research was conducted on eighth-grade students at SMP IT Miftahul Khoirot Pangkalpinang. Subsequently, students worked on individual tasks, namely pretest questions before working on LKPD and posttest questions after working on LKPD. The media used is LKPD. The results of this study indicate that students' learning activities using the context of traditional Palembang dance can help students understand the role of number sequences and solve problems related to number sequences in contextual problems.
Keywords: PMRI; Number Sequences; Traditional Palembang Dance